COGNITIVE BEHAVIORAL THERAPY (CBT) IN WOMEN DIAGNOSED WITH BINGE EATING DISORDER (BED): A LITERATURE REVIEW - Ribeiro, Valéria Cristina dos Santos; Favoretto, Miriele Valinhos; Massuia, Fernanda Aparecida de Ornelas; de Menezes, Cleidimar Borges; Pedroso, Brenda Torres; Figueiró, Rafael de Albuquerque (Seven Editora, 2025)
This study aimed to understand the cognitive, behavioral, physical, and environmental aspects of binge eating disorder (BED), identifying the main cognitive behavioral therapy (CBT) interventions for this disorder and the treatment’s impact on prognosis in female patients. The research followed a systematic review of qualitative literature, using databases such as PubMed, SciELO, Pepsic, Cochrane, BVS-Saúde, and LILACS, with descriptors “Binge Eating Disorder (BED)”, “Cognitive Behavioral Therapy (CBT)”, and “Binge Eating and Women” in Portuguese and English. Fifteen relevant articles were selected for the final analysis after applying inclusion and exclusion criteria. BED is a multifactorial disorder that can involve cognitive, behavioral, physical, and environmental aspects, influenced by dysfunctional beliefs about body image, low self-esteem, and stress. CBT proved effective in treating BED, employing techniques such as cognitive restructuring, self-monitoring, emotional regulation, mindfulness, emotional skills training, frustration tolerance strategies, psychoeducation, and problem-solving training. The effects include reduced binge episodes, improved self-esteem and quality of life, as well as a positive impact on prognosis by promoting emotional regulation and enhancing mental health. However, results varied among patients, suggesting that CBT should be combined with other interventions, such as nutritional support and physical follow-up.DOI: https://doi.org/10.56238/sevened2025.021-075